Risk factors for dysphagia after transoral videolaryngoscopic surgery for laryngeal and pharyngeal cancer. Issue 2 (22nd May 2015) - Tomifuji, Masayuki; Araki, Koji; Yamashita, Taku; Mizokami, Daisuke; Kamide, Daisuke; Suzuki, Hiroshi; Miyagawa, Yoshihiro; Tanaka, Shingo; Taniai, Shinichi; Shiotani, Akihiro
ABSTRACT: Background: Transoral surgery is gaining attention as a minimally invasive treatment option for laryngeal and pharyngeal cancer. Postoperative swallowing function is satisfactory in most cases, but occasionally dysphagia persists. Methods: Swallowing function of 86 patients who underwent transoral videolaryngoscopic surgery (TOVS) for laryngeal and pharyngeal cancers was evaluated by the Functional Outcome Swallowing Scale (FOSS) and risk factors for dysphagia were identified. Results: FOSS stage was 0 to 1 in 90%, 2 in 5.8%, 3 in 3.5%, and 4 in 1.2% of the patients. Only 1 patient had indication for percutaneous endoscopic gastrostomy (PEG). Univariate analysis revealed that resection of the pyriform sinus ( p = .0280) and arytenoid ( p = .0139), pulmonary dysfunction ( p = .0353), and large mucosal defect ( p = .0223) were associated with postoperative dysphagia. Conclusion: Although the rate of PEG dependency is low in transoral surgery, surgeons should mention the risk of postoperative dysphagia when counseling patients preoperatively. © 2015 Wiley Periodicals, Inc. Head Neck 38: 196–201, 2016